The Scaffold Protein IscU Retains a Structured Conformation in the FeS Cluster Assembly Complex. Issue 11 (8th July 2014) - Yan, Robert; Kelly, Geoff; Pastore, Annalisa
Abstract IscU and IscS are two essential proteins in the machine responsible for the biogenesis of iron–sulfur clusters, prosthetic groups that are involved in several essential functions. The scaffold protein IscU is the temporary acceptor of the cluster that results when the protein forms a 110 kDa complex with the desulfurase IscS. In the absence of zinc, which stabilises the folded state, IscU is present in solution in equilibrium between a structured and an unstructured form. It has been suggested that IscS preferentially binds unstructured IscU, although crystal structures indicate otherwise. To learn more about the IscS–IscU complex, we have used advanced solution NMR techniques to observe directly the state of fold of IscS‐bound IscU. We present unambiguous evidence that IscU is folded in the complex and that the unstructured form does not bind to IscS. Our data correlate with several observations and explain an IscU‐related pathology.